Lightweight Cryptography for the Encryption of Data Communication of IoT Devices - Ivan Sokol (MDPI AG, 2021)
We are at the beginning of the age of the Internet of things. Soon, we will be surrounded by smart homes, cities, and infrastructure. To achieve this vision, millions of devices will have to be able to communicate with each other. The demands for communication channels will increase significantly. An increasing amount of data will be transmitted with a requirement of minimal delay. The capacities of transmission systems can be quickly depleted. Building new communication channels is very time consuming but also financially demanding. To maximize existing infrastructure, we should pay attention today to the issue of transmitted data. One of the ways is to focus attention on reducing the volume of transmitted data. In this paper, we present a method of reducing the volume of data transmission between a server and an IoT device, focusing on the bandwidth, transmission security, and system resources of the IoT device. The required reduction is achieved by data compression and replacing the SSL/TLS cryptographic protocol with lightweight cryptography based on the Vernam cipher principle. The original SSL/TLS protocol is still used for device management needs only.